Musical Therapy with Balinese Flute Increased Cognitive Function, Brain-derived Neurotrophic Factor Serum Levels, and Decreased Interleukin-6 Serum Levels among the Elderly in West Denpasar Primary Health Clinic - Adnyana, I Made Oka; Mahadewi, Ni Putu Ayu Putri; Laksmidewi, A.A.A. Putri (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Studies have shown the effects of music toward improved cognitive function due to changes in molecular production and signaling through increased messenger secretion, including hormones, neurotransmitters, and growth factor proteins. Most of the studies used Western classical music as an intervention. AIM: We would like to investigate whether traditional Balinese flute musical composition entitled can improve cognitive function as well as brain-derived neurotrophic factor (BDNF) and interleukin (IL)-6 levels, on par with the Western classical composition. METHODS: This was a prospective intervention trial involving 40 participants recruited from Primary Health Clinic 2 in West Denpasar, Bali, and divided into two groups. Participants were asked to listen to either “Morning Happiness” by Mr. Agus Teja Sentosa, S. Sn (treatment), or Vivaldi’s composition of “Spring” (control group) for 20 min each day for 21 days. Cognitive evaluation was performed using Montreal Cognitive Assessment (MoCA)-INA and blood sample was withdrawn during the 1st day for BDNF and IL-6 levels measurement. All statistical analyses were conducted using IBM SPSS Statistics 20. RESULTS: There was a significant difference between initial and endpoint MoCA-INA test results among treatment and control group (p < 0.001), but there was no significant difference between control and treatment (p = 1.00). BDNF levels differed significantly between initial and endpoint BDNF levels among control group (p < 0.001), but did not differ significantly between control and treatment groups (p = 0.534). There was no significant difference between initial and endpoint IL-6 levels between the control group, but there was a close to statistical difference between of initial and endpoint IL-6 levels among the treatment group (p = 0.052). There was a significant difference in the memory domain between the control and treatment groups (p = 0.01) as measured using MoCA-INA questionnaire. CONCLUSION: Balinese traditional flute composition was proven to be non-inferior when compared with Western classical composition as it improved mainly memory domain accompanied by increasing BDNF and decreased IL-6 levels.